2003
DOI: 10.1108/02640470310499821
|View full text |Cite
|
Sign up to set email alerts
|

American Indian tribal Web sites: a review and comparison

Abstract: Many Native American tribes have Web sites, but the content of these sites varies depending on a number of factors, including the audience, purpose and context of the site, geographic distribution of tribal members, economic factors, tribal policies, and the digital divide. Some sites are geared primarily to non‐Native tourists and the general public, while others are designed to reach out to those tribal members who live far from Indian lands. Economic factors impact both the type of Web site the tribe can af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As noted in the previous study by Gaston Anderson (2003), most of the tribal websites provided genealogy, history, language, tribal government information, and community events. A few clusters of tribes shared similar informational homepage templates, usually provided by a coordinating regional agency.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As noted in the previous study by Gaston Anderson (2003), most of the tribal websites provided genealogy, history, language, tribal government information, and community events. A few clusters of tribes shared similar informational homepage templates, usually provided by a coordinating regional agency.…”
Section: Resultsmentioning
confidence: 95%
“…1 The sites serve many purposes, providing information to tribal members and non-Indians. An examination of 132 official tribal websites in 2003 found that the sites typically included information about genealogy, tribal history, native language, employment opportunities, community events, tribal government, health services, and economic development (Gaston Anderson, 2003).…”
Section: American Indian Identity On the Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…In informal discussions with Tribal leaders, we learned that there are various reasons why TRRBs may not have an online presence. Some TRRBs may lack the resources to establish and maintain a website and respond to the volume of research inquiries (Gaston Anderson, 2003). Despite these limitations, they may still want to strengthen their online presence to ensure that their research codes and protocols are respected.…”
Section: Rq1: Online Presencementioning
confidence: 99%